Global implications of the new WHO and UNICEF implementation guidance on the revised Baby-Friendly Hospital Initiative - Aryeetey, R.; Dykes, F. (Blackwell Publishing Ltd, 2018)
Although breastfeeding confers both short- and long-term benefits for children and their mothers, breastfeeding practice remains suboptimal, globally. In addition to barriers including misperceptions and inappropriate marketing of breast milk substitutes, inadequate support for breastfeeding remains a challenge in many settings. To improve access to appropriate health system support, the World Health Organization (WHO) has reviewed the Baby-Friendly Hospital Initiative (BFHI), which ensures provision of optimal clinical care and support to mothers and their infants. This review has resulted in revision of the Ten Steps to Successful Breastfeeding, which form the core standards of (BFHI). These now consist of critical management procedures to support breastfeeding (Steps 1 and 2) and key clinical practices to support breastfeeding (Steps 3-10). In Step 1, there is now specific emphasis on compliance with the WHO Code of Marketing of Breast-milk Substitutes and relevant World Health Assembly resolutions as well as on internal monitoring. There are also significant position shifts like the recommendation to “Counsel mothers on the use and risks of feeding bottles, teats, and pacifiers,” which is a departure from the earlier position of avoiding reference to these technologies. These revisions require countries and states to revise activities and tools for their local situation but without compromising the standards. © 2018 John Wiley & Sons Ltd
Keywords: Baby Friendly Hospital Initiative; Breastfeeding; Revised; Ten Steps; UNICEF; WHO